2018
DOI: 10.1111/sltb.12503
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes of Community‐Based Suicide Prevention Approaches That Involve Reducing Access to Pesticides: A Systematic Literature Review

Abstract: Our review identified three community interventions that show some promise for reducing pesticide suicides by restricting access to means, which will require replication in large, well-designed trials before they can be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…CIAT provides 24/7 telephone service to healthcare professionals and citizens calling 911 (emergency number) following an overdose or self-poisoning in order to receive support by emergency services if needed. Previous research shows that public and community-wide regulations which prioritize limited access to pesticides are effective interventions to treat suicides due to selfpoisoning (24). Furthermore, the establishment of toxicology centers is a commitment of all the states belonging to the WHO, which recognizes the impact on the management of poisonings, whether intentional or accidental.…”
Section: Comparison With Previous Researchmentioning
confidence: 99%
“…CIAT provides 24/7 telephone service to healthcare professionals and citizens calling 911 (emergency number) following an overdose or self-poisoning in order to receive support by emergency services if needed. Previous research shows that public and community-wide regulations which prioritize limited access to pesticides are effective interventions to treat suicides due to selfpoisoning (24). Furthermore, the establishment of toxicology centers is a commitment of all the states belonging to the WHO, which recognizes the impact on the management of poisonings, whether intentional or accidental.…”
Section: Comparison With Previous Researchmentioning
confidence: 99%
“…Unfortunatelyand importantly for the firearm suicide fieldrandomized controlled trials have not found evidence that these storage interventions reduced pesticide-related suicide rates (Pearson et al, 2017). A 2019 systematic review on pesticide suicide prevention concluded efforts focused on in-home storage should end, with energy instead shifted to community-based, centralized storage options (Reifels et al, 2019). Notably, this systematic review was funded by the pesticide industry and, while methodologically sound, overstated the promise of community-based programming (Knipe and Eddleston, 2019).…”
mentioning
confidence: 94%
“…We were pleased to see the methodologically sound systematic review of community-based interventions to reduce access to pesticides for pesticide-related suicide prevention published by Reifels et al (2018) in Suicide and Life-Threatening Behavior (in press). An estimated 110,000-168,000 people die by pesticide self-poisoning each year (Mew et al, 2017).…”
mentioning
confidence: 99%
“…Despite the authors presenting findings from the remaining "promising community-based interventions," the null findings from the larger trial cannot simply be ignored. The authors argue that instead of household safer storage of pesticides, community storage (similar to the pilot study by Vijayakumar et al (2013)) may be more effective in reducing pesticide self-poisoning by providing additional safeguards. This is unlikely, given that less than a quarter of households in intervention villages utilized the facility during the 1.5 years of followup, with 35% of households reporting that central storage was inconvenient for them.…”
mentioning
confidence: 99%
See 1 more Smart Citation